Immunological aspects and gender bias during respiratory viral infections including novel Coronavirus disease‐19 (COVID‐19): A scoping review. Issue 9 (19th May 2021) - Vadakedath, Sabitha; Kandi, Venkataramana; Mohapatra, Ranjan K.; Pinnelli, Venkata B. K.; Yegurla, Richa R.; Shahapur, Praveen R.; Godishala, Vikram; Natesan, Senthilkumar; Vora, Kranti S.; Sharun, Khan; Tiwari, Ruchi; Bilal, Muhammad; et al.
Abstract: The human immune system is not adequately equipped to eliminate new microbes and could result in serious damage on first exposure. This is primarily attributed to the exaggerated immune response (inflammatory disease), which may prove detrimental to the host, as evidenced by SARS‐CoV‐2 infection. From the experiences of Novel Coronavirus Disease‐19 to date, male patients are likely to suffer from high‐intensity inflammation and disease severity than the female population. Hormones are considered the significant pillars of sex differences responsible for the discrepancy in immune response exhibited by males and females. Females appear to be better equipped to counter invading respiratory viral pathogens, including the novel SARS‐CoV‐2, than males. It can be hypothesized that females are more shielded from disease severity, probably owing to the diverse action/influence of estrogen and other sex hormones on both cellular (thymus‐derived T lymphocytes) and humoral immunity (antibodies). Highlights: Hormones are considered as significant pillars of sex differences and influence both the innate as well as adaptive immune responses. Sex hormones and their potential role in the immune responses has not been completely understood. Females are more shielded from disease severity probably owing to their unique hormonal constitution. In females, the immunological cells have been noted to restrict the spread of infections as compared to males. Males suffer from increased severity of respiratory infections and are less prone to autoimmune disorders as compared to the female counterparts. Estrogen and other sex hormones play a key role both in restricting the inflammatory responses and in effective clearance of pathogens including the novel Coronairus.